The constitutional control system in Colombia - Luis Javier Moreno Ortiz (Civilizar, 2010)
The system of constitutional control in Colombia designed in the Legislative Act n.º 3 of 1910 is a milestone in a long and fruitful political and constitutional tradition owes much to his Hispanic roots and its American developments. Both the public action of unconstitutionality as the plea of unconstitutionality have clear precedents in the constitutionalism of Spain and the Colony were prepared by a Constituent Assembly acted with knowledge and faithfulness to that tradition and have been and are institutions of our capital social and democratic state of law.